Dual boundary element analysis of fatigue crack growth, interaction and linkup. (March 2016) - Santana, E.; Portela, A.
Abstract: Multiple-site and widespread fatigue damage have been an issue to the aircraft and construction industry for a long period. Structural components develop cracks at several locations which grow with crack paths that are difficult to predict. When two cracks approach one another, their stress fields influence each other leading to an enhancing or shielding effect which depends on the position and orientation of the cracks. Since there are no generalized analytical methods for predicting crack stress fields, simulation of multiple-crack growth is an important and challenging task which is still an evolving area of research. This paper describes a two-dimensional application of the dual boundary element method (DBEM) to the analysis of mixed-mode multiple-crack growth in linear elastic fracture mechanics, under fatigue loading. The crack-growth process is simulated with an incremental multiple-crack extension analysis based on the maximum principal stress criterion. For each increment of the analysis, in which crack extensions are modelled with new straight boundary elements, the DBEM is applied to perform a single-region stress analysis of the cracked structure and the J-integral is used to compute the stress intensity factors. The incremental analysis is based on a prediction–correction technique that defines, in each increment of the analysis, the direction and the extension of the multiple interacting cracks, thus taking into account the discreteness of the analysis and ensuring that the requirement of the path uniqueness is satisfied. Based on the ligament yield criterion which assumes that when the plastic zones of two adjacent cracks touch each other, the ligament between the cracks fails and the cracks coalesce, plates with multiple-site damage can be analysed. The fatigue life and residual strength of the structure are introduced as a post-processing procedure on the results of the multiple-crack growth. Results of this incremental analysis are presented for several geometries with multiple-site damage, demonstrating the accuracy and efficiency of the strategies adopted in the analysis.